Economic crisis, farming systems, and forest cover change in the humid forest zone of Cameroon - Sunderlin, William D.; Ndoye, O.; Bikie, H. (2000)
The rate of forest clearing by small farmers in the humid forest zone (HFZ) of Cameroon increased significantly in a period of economic crisis dating from 1986. A random sample survey of 648 households was conducted in 54 villages in the HFZ to understand the effect of the crisis and of a 1996 currency devaluation on the practices of small farmers, and the effect of these practices on forest cover change. Three hypotheses were tested: (1) the balance between export crop and food crop production; (2) the degree of market-orientation of food crop production; and (3) the gender division of labour. The key results are: (1) the area of cocoa production has stagnated while that of coffee, plantain and other food crops has tended to increase; (2) food crop production is now more market-oriented; and (3) more men are now far more involved in food crop production than in the past. The results corroborate other studies showing that increased deforestation in the HFZ is largely a product of these three factors and also of: increased rural population, partly resulting from urban-rural migration; decline of food imports and corresponding increase in food crop production; decreased government subsidies for agricultural inputs; and increased logging. The study concludes that: (1) macroeconomic instability can lead to unforeseen and grave consequences not only for the well-being of farmers but also for efforts to protect remaining tropical forests: and (2) crop diversification might be one way to help avert future income shocks to farmers and minimise forest clearing activity.